The Voltage-Gated Calcium Channel EGL-19 Acts on Glia to Drive Olfactory Adaptation - Chen, Du; Cheng, Hankui; Liu, Siyan; Al-Sheikh, Umar; Fan, Yuedan; Duan, Duo; Zou, Wenjuan; Zhu, Linhui; Kang, Lijun (Frontiers in Molecular Neuroscience, 2022)
Calcium channelopathies have been strongly linked to cardiovascular, muscular, neurological and psychiatric disorders. The voltage-gated calcium channels (VGCC) are vital transducers of membrane potential changes to facilitate the dynamics of calcium ions and release of neurotransmitter. Whether these channels function in the glial cell to mediate calcium variations and regulate behavioral outputs, is poorly understood. Our results showed that odorant and mechanical stimuli evoked robust calcium increases in the amphid sheath (AMsh) glia from C. elegans, which were largely dependent on the L-Type VGCC EGL-19. Moreover, EGL-19 modulates the morphologies of both ASH sensory neurons and AMsh glia. Tissue-specific knock-down of EGL-19 in AMsh glia regulated sensory adaptability of ASH neurons and promoted olfactory adaptation. Our results reveal a novel role of glial L-Type VGCC EGL-19 on olfaction, lead to improved understanding of the functions of VGCCs in sensory transduction.